Recognizing facial expressions of social emotions: do males and females differ? - Simão,Cláudia P. (2008)
Social behaviour plays an important role on individual’s interpersonal relations and it is mainly regulated by social emotions expression and recognition. This social emotional processing is distributed differently by gender relations and roles. In this sense, the main goal of this study was to assess gender differences in social emotion recognition. Three social emotions were selected (arrogance, guilt and jealousy) and assessed by a group of 60 participants (30 men and 30 women), using an emotion recognition paradigm. Results suggested that genders differ on emotion recognition. Overall females presented higher accuracy scores and inferior reaction times when compared to males. These findings suggest that emotional processing evolved to regulate social behaviour is based on gender roles.